Comparison Between HB and ISO Standard for Calculating Bevel Gear Tooth Surface Contact Fatigue Strength - Wenshuang Teng; Mei Guo; Zhenhai Song (Jixie chuandong)
In order to correctly evaluate the gear strength calculation results in different standards， the difference between Chinese aviation industry standard （HB） and international standardization organization standard （ISO） in calculating the load capacity of bevel gear tooth surface contact fatigue is analyzed and compared. Through the two ways of comparison of calculation methods and examples， the differences of the two standard calculation formulas， the types of correction coefficients， the differences in values and their effects on the calculation results are found out. The results show that the ISO standard considers more influence factors than the HB standard， and the range is wider. Especially， there is a great difference in the calculation of dynamic load coefficient， which makes the basic value of contact stress calculated by ISO standard smaller， the calculated contact stress equivalent， and the allowable contact stress larger.